2018
DOI: 10.1021/acs.molpharmaceut.8b00786
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Kinetic Stability of the Amorphous Phase of the Chloramphenicol Antibiotic

Abstract: We employ broadband dielectric spectroscopy to study the relaxation dynamics and crystallization kinetics of a broad-spectrum antibiotic, chloramphenicol, in its supercooled liquid form. Two dynamic processes are observed: the structural α relaxation, which becomes kinetically frozen at T g = 302 ± 1 K, and an intramolecular secondary relaxation. Under isothermal conditions, the supercooled drug displays interconversion between different isomers, followed by recrystallization. Recrystallization follows the Avr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
(127 reference statements)
2
15
0
1
Order By: Relevance
“…In some cases, the secondary relaxation corresponds to "intramolecular" motions involving a relative motion of polar sidegroups of a polymer chain (as in polyvynilpirrolidone (Romanini et al, 2018)) or of a subpart of a molecule (as it is the case for the chloramphenicol molecule (Rivas et al, 2018) and other drugs (Tripathi et al, 2015)). In other cases, the secondary relaxation involves the rigid reorientation of the whole molecule or chain segment, as the cooperative α relaxation but involving only local degrees of freedom (Ngai and Paluch, 2004).…”
Section: Bds Studymentioning
confidence: 99%
See 3 more Smart Citations
“…In some cases, the secondary relaxation corresponds to "intramolecular" motions involving a relative motion of polar sidegroups of a polymer chain (as in polyvynilpirrolidone (Romanini et al, 2018)) or of a subpart of a molecule (as it is the case for the chloramphenicol molecule (Rivas et al, 2018) and other drugs (Tripathi et al, 2015)). In other cases, the secondary relaxation involves the rigid reorientation of the whole molecule or chain segment, as the cooperative α relaxation but involving only local degrees of freedom (Ngai and Paluch, 2004).…”
Section: Bds Studymentioning
confidence: 99%
“…In other cases, the secondary relaxation involves the rigid reorientation of the whole molecule or chain segment, as the cooperative α relaxation but involving only local degrees of freedom (Ngai and Paluch, 2004). The latter secondary relaxations are termed Johari-Goldstein relaxations (Johari and Goldstein, 1970), and they are observed for example in fully rigid molecules (Romanini et al, 2012) and in polymers with monoatomic or methyl sidegroups such as polybutadiene (Schroeder et al, 2007) and 1,4polyisoprene (Roland et al, 2004), but they are also observed together with intramolecular modes in other polymers (Romanini et al, 2018;Cerveny et al, 2008).…”
Section: Bds Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Dielectric spectroscopy is a versatile tool that provides useful information on the intensity (dielectric strength) and relaxation time of the macromolecular dynamic processes . In addition, the dielectric analysis of heterogeneous materials allows studying interfacial effects such as Maxwell–Wagner–Sillars (MWS) relaxations .…”
Section: Introductionmentioning
confidence: 99%